Intracranial hypertension and papilloedema as a complication to low antiretroviral therapy adherence in a man living with chronic HIV. Issue 3 (16th March 2021) - Gynthersen, Rosa Maja Møhring; Mens, Helene; Wegener, Marianne; Wareham, Neval Ete
Abstract : We describe a 61-year-old man living with HIV on antiretroviral therapy (ART), who presented with headache, dizziness and blurred vision. Latest CD4 + cell count 3 months prior to admission was 570×10 6 cells/mL and HIV viral load <20 copies/mL. The patient was diagnosed with cerebrospinal fluid (CSF) lymphocytic pleocytosis, raised intracranial pressure and papilloedema. Neuroimaging showed normal ventricular volume and no mass lesions, suggesting (1) neuroinfection (2) idiopathic intracranial hypertension or (3) retroviral rebound syndrome (RRS) as possible causes. Neuroinfection was ruled out and idiopathic intracranial hypertension seemed unlikely. Elevated plasma HIV RNA level was detected consistent with reduced ART adherence prior to admission. RRS is a virological rebound after ART interruption, which can mimic the acute retroviral syndrome of acute primary infection. To the best of our knowledge, we describe the second case of RRS presenting as CSF lymphocytic pleocytosis and elevated intracranial pressure after low ART adherence.